# 2 n 1 2 n n n 1 so we can pick 0 to make

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: /µn 1 )⇡ (n n2 µn 1 · ⇡ (n 2) and it follows that 2) Repeating the last reasoning leads to ⇡ (n) = n 1 · n 2 ··· 0 ⇡ (0) µn · µn 1 · · · µ1 (4.18) To check this formula and help remember it, note that (i) there are n terms in the numerator and in the denominator, and (ii) if the state space was {0, 1, . . . , n}, then µ0 = 0 and n = 0, so these terms cannot appear in the formula. To illustrate the use of (4.18) we will consider several concrete examples. Example 4.13. Two state chains. Suppose that the state space is {1, 2}, q (1, 2) = , and q (2, 1) = µ, where both rates are positive. The equations ⇡ Q = 0 can be written as ✓ ◆ ⇡1 ⇡ 2 =0 0 µ µ The ﬁrst equation says ⇡1 + µ⇡2 = 0. Taking into account that we must have ⇡1 + ⇡2 = 1, it follows that ⇡1 = µ +µ and ⇡2 = +µ Example 4.14. Barbershop. A barber can cut hair at rate 3, where the units are people per hour, i.e., each haircut requires an exponentially distributed amount of time with mean 20 minutes. Suppo...
View Full Document

Ask a homework question - tutors are online